Binding of plasma factor XIII to thrombin-receptor activated human platelets - Nagy, Béla, Jr; Simon, Zsuzsa; Bagoly, Zsuzsa; Muszbek, László; Kappelmayer, János (Thrombosis and Haemostasis, 2009)
Platelet-bound coagulation factor XIII (FXIII) is targeted and concentrated at the site where platelet-rich thrombi are formed. Previous studies were in disagreement about the nature of FXIII binding to platelets. In this study, thrombin-receptor activating peptide (TRAP)-stimulated human whole blood and washed platelets were analysed by flow cytometry for the binding of FXIII using a monoclonal antibody against the A subunit of FXIII (FXIII-A). Here, we demonstrate that FXIII-A positivity significantly increased on activated platelets in whole blood compared to unstimulated sample, but not in washed platelets. GPIIb/IIIa receptor plays an essential role in FXIII binding, as fibrinogen receptor antagonist eptifibatide and fibrinogen binding inhibitor RGDS tetrapeptide significantly prevented the binding of FXIII. Furthermore, stimulated platelets from a patient with severe type I Glanzmann thrombasthenia showed insignificant FXIII-A positivity versus healthy controls. In addition, basal negligible amount of FXIII on washed platelets was only slightly increased when highly purified plasma FXIII (FXIII-A2B2) was added upon platelet activation by TRAP. Similarly, no remarkable FXIII-A positivity was observed when we used FXIII-A2B2 with γA/γA fibrinogen. However, γA/γ' fibrinogen significantly augmented FXIII binding on TRAP-stimulated platelets in the presence of non-activated FXIII-A2B2. We conclude that FXIII-A2B2 of plasma origin binds to thrombin-receptor activated platelets via GPIIb/IIIa receptor-bound fibrinogen with γ’-chain and is not capable of direct platelet binding.
Keywords: Factor XIII; platelet activation; TRAP; fibrinogen